(untitled) (Jurnal Bahasa, 2018)
This paper intends to describe and explain the syllable structure in the Kuala Pilah Malay dialect. Data for this study were obtained from field work conducted in Kampung Ulu Gentam, Kuala Pilah. Previous analyses of Malay basic syllable structures show that the language consists of four types of syllable structures i.e. CV, CVC, V and VC. The finding of this study demonstrates there is a difference in the constraint ranking that in the syllable structure of the Kuala Pilah dialect compared to standard Malay. Apart from this, the results of this study also show that different strategies are employed in the construction of vowel and consonant-initial syllable structures. The basic construction of syllable is formed by the constraints named ONSET and *CODA, and all the patterns of syllables obey these constraints. A set of hierarchical constraints of Kuala Pilah Malay dialect yielded *COMPLEXCODA >> CONTIGUITY >> ALIGN-L >>DEP-IO >> ONSET >> MAX-IO. Any similarities found in the patterns of syllables between this dialect and standard Malay were analysed as the result of difference in the ranking of well-formedness constraints in the grammar of particular dialects. Keywords: Malay dialect, Kuala Pilah, syllable structure, phonology, optimality theory